A phylogeny reconstruction of the Dendrophylliidae (Cnidaria, Scleractinia) based on molecular and micromorphological criteria, and its ecological implications. (23rd July 2014) - Arrigoni, Roberto; Kitano, Yuko F.; Stolarski, Jaroslaw; Hoeksema, Bert W.; Fukami, Hironobu; Stefani, Fabrizio; Galli, Paolo; Montano, Simone; Castoldi, Elisa; Benzoni, Francesca
<x xml:space="preserve">Abstract</x> Recent molecular phylogenetic studies have shown that most traditional families of zooxanthellate shallow‐water scleractinians are polyphyletic, whereas most families mainly composed of deep‐sea and azooxanthellate species are monophyletic. In this context, the family Dendrophylliidae (Cnidaria, Scleractinia) has unique features. It shows a remarkable variation of morphological and ecological traits by including species that are either colonial or solitary, zooxanthellate or azooxanthellate, and inhabiting shallow or deep water. Despite this morphological heterogeneity, recent molecular works have confirmed that this family is monophyletic. Nevertheless, what so far is known about the evolutionary relationships within this family, is predominantly based on skeleton macromorphology, while most of its species have remained unstudied from a molecular point of view. Therefore, we analysed 11 dendrophylliid genera, four of which were investigated for the first time, and 30 species at molecular, micromorphological and microstructural levels. We present a robust molecular phylogeny reconstruction based on two mitochondrial markers (COI and the intergenic spacer between COI and 16S) and one nuclear (rDNA), which is used as basis to compare micromorphogical and microstructural character states within the family. The monophyly of the Dendrophylliidae is well supported by molecular data and also by the presence of rapid accretion deposits, which are ca. 5 μm in diameter and arranged in irregular clusters, and fibres that thicken the skeleton organized in small patches of a few micrometres in diameter. However, all genera represented by at least two species are not monophyletic, Tubastraea excluded. They were defined by traditional macromorphological characters that appear affected by convergence, homoplasy and intraspecific variation. Micromorphogical and microstructural analyses do not support the distinction of clades, with the exception of the organization of thickening deposits for the Tubastraea clade.